EVALUASI NON PERFORMING LOAN PADAPT. BPR TANAOBA LAIS MANEKAT CABANG KUPANG - Tedju, Debriyanti Christanti (P3M- Politeknik Negeri Kupang, 2019)
Abstract This research used quantitative research. Primary data was obtained directly from the company's financial department including financial statements and balance sheets in 2013-2018. The data analysis method used was non-performing loans, which is a comparison between bad loans and loans. The results showed that the percentage of non-performing loans increased and also decreased each year. In 2014,the amounti was 6.35%. For 2015, 8.15%. It was still stable so that it is statedto be healthy. In 2016, it rose to 10.94% then for 2017, it dropped to 10.66% so it is stated to be quite healthy.In 2018, it dropped to 8.52%. This has got an effect on the condition of bad loans.It was high but has decreased as well as increased during 2014-2018. It is stated that it affects the condition of the bank's quality level. Keywords: Bad Credit, Non Performing Loans (NPL)